Treating Different Diseases With the Same Method—A Traditional Chinese Medicine Concept Analyzed for Its Biological Basis - Zhai, Xing; Wang, Xi; Wang, Li; Xiu, Linlin; Wang, Weilu; Pang, Xiaohan (Frontiers in Pharmacology, 2020)
Traditional Chinese medicine (TCM) believes when the pathogenesis of the disease is the same or similar, similar syndromes will appear. The TCM principle "Curing different diseases with the same treatment" means that if different diseases have similar pathological changes in different stages of development, the same treatment principle and method can be used. It is a new way of studying TCM syndrome from the molecular level, to clarify its internal biological basis, so as to make the syndrome research objective, quantitative and standardized. Objective: Taking the syndrome of Qi deficiency and blood stasis of coronary heart disease and apoplexy as examples, taking their common mechanism as the breakthrough point, combining the complex network theory and information extraction technology, to mine the genes specifically relevant to the target syndromes. Through the analysis of the core network to explore the correlation between biological indicators of different diseases, revealing the scientific connotation. Methods: To establish the data dictionary of the disease genes and the thesaurus of characterization terms of the target syndrome, to mine the most related NEI genes by means of gene entity recognition, complex network construction, network integration and decomposition, to select traditional Chinese material medicine most relevant to the target syndromes through TCMIP v2.0 platform, so as to study the biological basis of "Curing different diseases with the same treatment" from the medicine and molecular level. Results: 46 genes were involved in the target syndromes, including IL-10, Foxp3, Bcl-2, AKT1, clcf1, HGF, EGF, IGF1, CXCR4, CTNNB1, CNTF, BDNF, GDNF, etc. It can be inferred that inflammatory response, apoptosis, proliferation and other mechanisms may be the same molecular mechanism. Conclusion: It is feasible to use information extraction and complex network technology to find syndrome biological indicators. The implementation of this method will provide a new method for the research of syndrome objectification in the era of big data, and an advanced, effective and concise path for the TCM objectification and internationalization.